Delegitimisation of Indonesian Traditional Leaders: An Analysis in Minangkabau, West Sumatra Province - Asrinaldi, Asrinaldi (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
It is argued that an excessive euphoria of autonomy was the primary consequence of the first five years of decentralisation in Indonesia after the New Order. The euphoria of autonomy led to the emergence of ethnic nationalism perpetuated by traditional powers that regulated the control and exploitation of natural resources. The New Order government tried to control local democratic practices by weakening traditional leaders' legitimacy. This article explains how this reality occurs in West Sumatra Province. First, based on village and regional government laws following the New Order, local democracy led to the delegitimisation of traditional power. Second, the systematic implementation of local democracy erased the traditional leadership authority that relegated the Minangkabau ethnic and traditional values. It was concluded that the government enacted the local government and village laws to regulate the traditional authority.